2021
DOI: 10.36740/wlek202103240
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Autoimmunity in Implantation Failure: A Literature Review

Abstract: The aim: This review was aimed to understand the role of different types of autoantibodies like antiphospholipid, antithyroid, antisperm, antinuclear, anti-ovarian autoantibodies and heat shock protein HSP 60 in the process of implantation in the normal way of conceiving and IVF and also to estimate that how the presence of these autoantibodies affect the normal pregnancy outcome. Materials and methods: This review process performed in the obstetrics and gynaecology postgraduate department, Bogomolets nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
0
5
0
2
Order By: Relevance
“…ICSI is therefore recommended, but studies have also found little difference in outcome between the use of IVF and ICSI ( 14 ). Some studies have found that autoimmune disorders also affect couples of reproductive age, such as the formation of anti-sperm antibodies detected in women with unexplained infertility ( 40 ). Which interfere with sperm penetration of the zona pellucida and cause IVF failure ( 39 ), and as research continues to be uncovered, it has been found that ICSI may overcome the problems posed by ASA ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…ICSI is therefore recommended, but studies have also found little difference in outcome between the use of IVF and ICSI ( 14 ). Some studies have found that autoimmune disorders also affect couples of reproductive age, such as the formation of anti-sperm antibodies detected in women with unexplained infertility ( 40 ). Which interfere with sperm penetration of the zona pellucida and cause IVF failure ( 39 ), and as research continues to be uncovered, it has been found that ICSI may overcome the problems posed by ASA ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…More and more clinical researchers are paying attention to the relationship between autoimmunity and infertility 24 . Almost all autoimmune diseases are associated with circulating autoantibodies directed against self‐proteins.…”
Section: Discussionmentioning
confidence: 99%
“…With the exposure of these antigens to immune cells, antisperm antibodies (ASAs) are naturally formed. ASAs have been detected in men with infertility and women with unexplained infertility [ 71 ]. Antibodies in the semen may negatively interfere with the fertilization process through various mechanisms, such as inhibition of sperm motility and sperm progression through the female genital tract, altered acrosomal reactions, or binding to zona pellucida [ 72 ].…”
Section: Conventional Ivf Art Indications and Clinical Situationsmentioning
confidence: 99%